Highly Efficient Production of Soluble Proteins from Insoluble Inclusion Bodies by a Two-Step-Denaturing and Refolding Method - Yang, Zhong; Zhang, Linlin; Zhang, Yan; Zhang, Ting; Feng, Yanye; Lu, Xiuxiu; Lan, Wenxian; Wang, Jufang; Wu, Houming; Cao, Chunyang; Wang, Xiaoning (PLOS ONE, 2011)
The production of recombinant proteins in a large scale is important for protein functional and structural studies, particularly by using Escherichia coli over-expression systems; however, approximate 70% of recombinant proteins are over-expressed as insoluble inclusion bodies. Here we presented an efficient method for generating soluble proteins from inclusion bodies by using two steps of denaturation and one step of refolding. We first demonstrated the advantages of this method over a conventional procedure with one denaturation step and one refolding step using three proteins with different folding properties. The refolded proteins were found to be active using in vitro tests and a bioassay. We then tested the general applicability of this method by analyzing 88 proteins from human and other organisms, all of which were expressed as inclusion bodies. We found that about 76% of these proteins were refolded with an average of >75% yield of soluble proteins. This “two-step-denaturing and refolding” (2DR) method is simple, highly efficient and generally applicable; it can be utilized to obtain active recombinant proteins for both basic research and industrial purposes.